آليات الحجاج شبه المنطقية في خطب البشير الإبراهيمي - طرش، علي (جامعة غرداية, 2021)
يهدف البحث إلى تتبع آليات الحجاج في الخطاب الإصلاحي في فترة الاستعمار من خلال خطب واحد من أهم رواد الإصلاح في الجزائر وهو البشير الإبراهيمي، عضو جمعية العلماء المسلمين الجزائريين، وذلك لمعرفة أهم المرتكزات المعرفية التي استند إليها الخطاب للوصول إلى عمق المجتمع الجزائري والتأثير فيه للحفاظ على الخصائص الوطنية المميزة، والتصدي للمستعمر. وقد وصل البحث إلى جملة من النتائج، لعل أبرزها هو اعتماد المرجعية الإسلامية في المحاججة، وذلك للوصول إلى أكبر قدر ممكن من الشعب، كما أن الحجاج عنده نشاط إقناعي يتخذ صورة خطاب إصلاحي تشكله عوامل ذاتية واجتماعية ومعرفية، وتحدده قدرات بلاغية وظفت كل العوامل المتاحة من قبله للوصول إلى غايات محددة.
The research aims to follow the mechanisms of reform discourse in the colonial period through the speeches of one of the most important pioneers of reform in Algeria, Al Bashir Al-Ibrahimi. He was member of the Association of Algerian Muslim Scholars. In order to know the most important Knowledge bases on which the discourse was based to reach the minds of Algerian society and influence it to preserve the distinctive national characteristics, and to stand up to the colonizer. The research reached a number of results, perhaps the most prominent is the adoption of Islamic reference to argue in order to reach as many people as possible. Moreover, arguing has a convincing activity that takes the form of a reform discourse which is constituted by subjective, social ,and cognitive factors ; and it is defined by rhetorical capacities that employed all the factors available to it to reach specific targets
Keywords: الخطاب الحجاجي -- اللسانيات اللغوية -- العلوم الشرعية -- اللغة العربية